Comparative analysis of weight-bearing function of lower extremities in children with recurrences of congenital equinovarus clubfoot after surgical treatment by «traditional» methods and Ponseti method - Khmyzov, Sergij; Kykosh, Genadij; Karpinska, Olena; Karpinsky, Mykhaylo (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2021)
Congenital equinovarus clubfoot (EVC) is the second most common congenital anomaly of the musculoskeletal system in children and one of the most common causes of childhood disability in Ukraine. The frequency of EVC reaches 1–3 cases per 1 000 newborns (35–40 % of all foot deformities). Objective. To determine the features of the children ability with EVC recurrences, before and after surgical treatment by «traditional» methods and Ponseti method. Methods. Biomechanical examinations of 65 children with EVC recurrences were performed. They were divided into two groups: group I (33 patients) — treated by «traditional» methods, which provided initial surgery, in order to completely correct all components of the deformity; group II (32 patients) — treatment by Ponseti method. Weight-bearing function was studied for all patients, before treatment, after 6 and 12 months after surgery, with statography. Results. It was determined that the standing parameters in the groups were not statistically different. After 6 months after the treatment, according to the statograms, the weight-bearing displacement remained, under the conditions of two weight-bearing standing towards the contralateral limb, in both groups of patients. In group I, after treatment, this parameter did not change (p = 0.924), and in group II it decreased by (2.7 ± 4.7) % (p = 0.013). Weight-bearing on the operated limb in both groups, in 12 months from surgery increased by 45 %. Conclusions. In patients, after treatment of EVC recurrences by Ponseti method, the weight-bearing function indicators, in the case of two weight-bearing standing, changed statistically significant. During the recovery process, when patients began to load the operated foot, a slight deterioration of standing parameters was observed in patients of group I in 6 months from surgery. In patients of group II, a complete restoration of statographic parameters occurred earlier, in 6 months, a normalization of weight-bearing and stability was observed. Thus, it can be argued that the use of Ponseti method in the complex treatment of EVC allows to restore the ability of weight bearing much earlier than with the «traditional» method. Key words. Congenital talipes equinovarus, children, Ponseti method, statography.